REPRESENTATION OF CULTURAL ROOTS IN MIRA NAIR’S FILM THE NAMESAKE - P, Vijay; M, Vijayakumar (International Journal of Psychosocial Rehabilitation, 2020)
Jhumpa Lahiri is one of the tremendous Indo-American novelists writing in English. She has written in her novels about the cross-cultural experiences of Indians and the exploration of their nativity. Lahiri’s novel, The Namesake accounts in detail the experiences of immigrant Indians in the United States. The Bollywood Director Mira Nair has directed an English film The Namesake based on Jhumpa Lahiri’s novel The Namesake. The movie The Namesake was released in 2006. The story was scripted by Sooni Taraporevala. The writer and the director of the story portray cautiously the Indian culture among the American Indians and the different attitude of the young generation of the American born Indians towards their parents. The Indians move to other countries for education, job, the welfare of the family and business. They also sacrifice their own air, food, soil, happiness and the family circumstances in the foreign land, which is clearly portrayed in the movie. This paper brings out the difficulties encountered by the first and the second generation Indian Americans in the United States and their struggle to be true to their native land and culture.